2013
DOI: 10.1002/pi.4528
|View full text |Cite
|
Sign up to set email alerts
|

In situ thermal reduction of graphene oxide in a styrene-ethylene/butylene-styrene triblock copolymer via melt blending

Abstract: We report an insitu thermal reduction of graphene oxide (GO) in a styrene-ethylene/butylene-styrene (SEBS) triblock copolymer matrix during a melt-blending process. A relatively high degree of reduction was achieved by melt-blending premixed GO/SEBS nanocomposites in a Haake mixer for 25 min at 225 • C. Infrared spectral results revealed the successful thermal reduction of, and the strong adsorption of SEBS on, the graphene sheets. The glass transition temperature of polystyrene (PS) segments in SEBS was enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Due to the excellent dispersion of CNTs, the electrical percolation threshold of the nanocomposite was approximately 0.5 wt%, much lower than the value of 3.5 wt% for nanocomposites fabricated by direct melt mixing [86]. Production of styrene-ethylene-1-butene-styrene block copolymer elastomer (SEBS)/graphene [87], NR/graphene [88], NBR/CNTs [86], and PU/graphene [89] nanocomposites with satisfactory filler dispersion using the masterbatch process has also been reported.…”
Section: Masterbatchmentioning
confidence: 99%
“…Due to the excellent dispersion of CNTs, the electrical percolation threshold of the nanocomposite was approximately 0.5 wt%, much lower than the value of 3.5 wt% for nanocomposites fabricated by direct melt mixing [86]. Production of styrene-ethylene-1-butene-styrene block copolymer elastomer (SEBS)/graphene [87], NR/graphene [88], NBR/CNTs [86], and PU/graphene [89] nanocomposites with satisfactory filler dispersion using the masterbatch process has also been reported.…”
Section: Masterbatchmentioning
confidence: 99%
“…As a layered carbon nanomaterial with high aspect ratio and excellent electronic, mechanical and thermal properties [1,2], graphene is widely used in improving electrical, mechanical, and thermal properties of polymers [3][4][5][6][7][8][9][10][11]. Many studies have shown improved electrical conductivities and mechanical performances for rigid epoxy/graphene nanocomposites [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] It is envisaged that its large specic area and the oxygen functionalities in graphene allow the enhanced interactions with the polymeric matrix and consequently the better thermal, mechanical, conductive properties. [25][26][27][28][29] It is envisaged that its large specic area and the oxygen functionalities in graphene allow the enhanced interactions with the polymeric matrix and consequently the better thermal, mechanical, conductive properties.…”
Section: Introductionmentioning
confidence: 99%